Preliminary Phytochemical Screening and in vitro Antioxidant Capacity of Some Traditional Medicinal Plants of Bangladesh (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Abstract not availableDhaka Univ. J. Pharm. Sci. 23(2): 205-209, 2024 (December)